Perancangan Sistem Informasi Presensi Peserta Praktikum Di Fakultas Teknik Universitas Sebelas Maret Surakarta - suparmo Suparmo (Indonesian Journal of Information Technology and Computing (IMAGING), 2023)
Sebelas Maret University Surakarta (UNS) applies an assessment system for student attendance in attending practicum lessons by 75%. In many cases, students who are not present can entrust attendance signatures to their friends to fill out the attendance list that is circulated in the practicum class. This is one of the factors that makes the assessment of student knowledge and competence doubtful. Another problem that exists in the presence section is the absence of a computerized attendance system equipped with automated attendance data calculations. The current attendance system only utilizes the Microsoft Excel application, whose report generation still uses manual input. This can allow for errors in inputting student attendance data. Based on the description of the background, it can be formulated the problem to be solved in this research is "How to design a student attendance information system in the scope of the Faculty of Engineering UNS". Limitations The problem that the author discusses in the study focuses more on the process of recording student attendance in accordance with the practicum schedule in the Civil Engineering laboratory. The method used for designing student attendance information systems uses the Waterfall Model System Development Life Cycle (SDLC). The programming language used is PHP and MySQL database. The design of this attendance information system is expected to prevent fraud committed by students in terms of attendance, for example such as attendance deposit. Student attendance data that can be entered into this information system is only students who attend the practicum in the civil engineering laboratory according to a predetermined schedule.